Addressing cardio-metabolic risks in type 2 diabetes: evidence-based insights on efpeglenatide - Kumar, Rajesh; Singh, Sunil Kumar; Singh, Shruti; Kumar , Alok (International Journal of Basic & Clinical Pharmacology, 2025)
Type 2 diabetes (T2D) is a chronic metabolic disorder linked to significant complications, including cardiovascular disease (CVD) and chronic kidney disease (CKD). Efpeglenatide, a long-acting glucagon-like peptide-1 receptor agonist (GLP-1 RA), has emerged as a promising therapy for addressing glycemic control, weight management, and cardio metabolic risks. A systematic review of randomized controlled trials (RCTs) was conducted using PRISMA guidelines. Searches in PubMed, Google Scholar, and Science Direct identified studies on efpeglenatide impact on T2D outcomes. Data on efficacy, safety, dose-response, and combination with sodium-glucose cotransporter-2 (SGLT2) inhibitors were extracted and analyzed. Out of 843 studies screened, 10 were included. The AMPLITUDE-O trial showed a 27% reduction in major adverse cardiovascular events (MACEs) (hazard ratio [HR]: 0.73, p=0.007) and significant renal benefits (HR: 0.68, p<0.001). Phase 2 trials demonstrated HbA1c reductions (0.6%-1.2%) and weight loss (up to 7.5%). Gastrointestinal side effects were common but mild to moderate, with no major safety concerns. Sub-analyses indicated that combining efpeglenatide with SGLT2 inhibitors did not diminish its efficacy, suggesting potential synergy in reducing cardio metabolic risks. Efpeglenatide demonstrates robust efficacy in glycemic control, weight loss, and reducing cardiovascular and renal risks, with a tolerable safety profile. Its long-acting properties and compatibility with SGLT2 inhibitors support its use in comprehensive, individualized T2D management. Further research is warranted to refine dosing strategies and evaluate long-term outcomes in diverse patient populations.